Local support mechanisms for entrepreneurship: The approach of local development and innovation institutions - F. Katimertzopoulos; Ch. Vlados (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose : The growth potential of SMEs entrepreneurship is examined at regional and local level, initially on a Global scale and then for the case of Greece. Additionally, the possibility of an economic development policy beyond the macroeconomic approach is examined, focusing on business growth and competitiveness in the light of meso and micro-economic policy approach. Design/methodology/approach: This research leads to the proposal of building knowledge mechanisms and direct and efficient systematic development and innovation at the local level, particularity during a time of economic crisis. The establishment of Institutes of Local Development and Innovation (ITAK) is primarily geared towards promoting innovative entrepreneurship and extroversion of locally installed businesses. As part of the proposal for the establishment of ITAK, a questionnaire was developed - a tool to initially measure companies' opinions on the need for outside help in the macro, meso and micro environment, in order to demonstrate that ITAK local-level structures could be developed. Findings: The survey results were accrued via the analysis of questionnaires distributed to companies. The results of the questionnaires in the micro-environment in relation to those in the macro-environment shows a lower tendency to change business, which may be because managers perceive economics several times more in macroeconomic terms rather than in meso and micro economic (terms). Research limitations/implications: The restrictions of this particular research are the small sample of study of businesses in one country (Greece); this is because the approach of study, which is quantitative-qualitative, limits analysis to small data sets in the current phase. Originality/value: The results in the micro-environment, in relation to those at macro-environmental, shows a lower tendency to change business, something which may be because managers perceive economics several times more in macroeconomic terms, rather than in meso and micro economic (terms).
Keywords: M12; M54; O15; 330; Local development policy; local entrepreneurship; business ecosystem; small enterprises